Analisis Pengaruh Lingkungan Kerja, Kompensasi Terhadap Kinerja Tenaga Pendidik Melalui Kepuasan Kerja Sebagai Variabel Intervening Di Era Covid-19 - Wisnu Hutama, Ranggi Rahadian; Tiarapuspa, Tiarapuspa; HS, Ikhwan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The method in this study uses quantitative analysis using a saturated sampling technique of 101 respondents through the distribution of questionnaires via google-form. The independent variables in this study are work environment, compensation, job satisfaction and the dependent variable is performance. The measurement variable uses a Likert scale. Data analysis was performed using descriptive statistical data analysis methods (mean) and structural equation model analysis (SEM). The test results in this study indicate that job satisfaction is an intervention variable on the effect of work environment and compensation on performance. Work environment and compensation have a positive and significant effect on performance. Work environment, compensation, satisfaction and performance both have a positive and significant influence. Based on the results of the analysis of the work environment in educational foundations that apply this, it can be used as the basis for creating a comfortable, safe, peaceful and safe work environment so that the goals of the foundation can be achieved optimally when the work environment is very supportive, allowing for binding performance and both of these are good work environments. and performance can also be or can be passed through indirect satisfaction